2009
DOI: 10.1007/s11661-009-9949-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Standard Heat Treatment Effects on Microstructure and Mechanical Properties of Laser Net Shape Manufactured INCONEL 718

Abstract: Laser net shape manufacturing (LNSM) is a laser cladding/deposition based technology, which can fabricate and repair near-net-shape high-performance components directly from metal powders. Characterizing mechanical properties of the laser net shape manufactured components is prerequisite to the applications of LNSM in aircraft engine industrial productions. Nickelbased superalloys such as INCONEL 718 are the most commonly used metal materials in aircraft engine high-performance components. In this study, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
209
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 463 publications
(256 citation statements)
references
References 11 publications
21
209
1
2
Order By: Relevance
“…EDS analysis showed that the atomic ratio of Fe:Nb in the white plate-like phase observed in homogenized specimens (Spot 5 in Figure 6) is 2.5:1. Although the plate-like phase could not be detected by X-ray diffraction due to a relatively small amount of precipitates, its morphology and composition are comparable with the Laves phase reported in the literature [3,19]. Qi et al [3] reported the partial dissolution of the Laves phase during solution treatment at 980 °C of laser net shape manufactured specimens.…”
Section: Phase Analysis Of Heat-treated Inconel 718supporting
confidence: 59%
See 3 more Smart Citations
“…EDS analysis showed that the atomic ratio of Fe:Nb in the white plate-like phase observed in homogenized specimens (Spot 5 in Figure 6) is 2.5:1. Although the plate-like phase could not be detected by X-ray diffraction due to a relatively small amount of precipitates, its morphology and composition are comparable with the Laves phase reported in the literature [3,19]. Qi et al [3] reported the partial dissolution of the Laves phase during solution treatment at 980 °C of laser net shape manufactured specimens.…”
Section: Phase Analysis Of Heat-treated Inconel 718supporting
confidence: 59%
“…Although the plate-like phase could not be detected by X-ray diffraction due to a relatively small amount of precipitates, its morphology and composition are comparable with the Laves phase reported in the literature [3,19]. Qi et al [3] reported the partial dissolution of the Laves phase during solution treatment at 980 °C of laser net shape manufactured specimens. Zhang et al [19] similarly observed incomplete dissolution of Laves phase in SLM specimens after solution treatment at 980 °C and double aging at 720 °C.…”
Section: Phase Analysis Of Heat-treated Inconel 718supporting
confidence: 59%
See 2 more Smart Citations
“…The powder morphology largely depends on the powder manufacturing process: gas atomization (GA) powders are generally in spherical shape but are mostly attached with small satellite particles, rotary atomization (RA) powders are basically semi-spherical, while plasma rotating electrode process (PREP) powders are almost perfect round without satellites [53]. In addition, gas induced porosity is common in GA and RA powders, while PREP powder is noted as absent from such porosity [53][54][55]. For the aforementioned reasons, PREP powders are preferred.…”
Section: Applying Powder Layermentioning
confidence: 99%